A Systematic Review of Pharmacist-Led Antimicrobial Stewardship Programs in Sub-Saharan Africa - Phanice Ajore Otieno; Sue Campbell; Sonny Maley; Tom Obinju Arunga; Mitchel Otieno Okumu (International Journal of Clinical Practice, 2022)
Background. The misuse of antibiotics contributes significantly to antimicrobial resistance (AMR). Higher treatment costs, longer hospital stays, and clinical failure can all result from AMR. According to projections, Africa and Asia will bear the heaviest burden of AMR-related mortalities in the coming years. Antimicrobial stewardship (AMS) programmes are therefore critical in mitigating the effects of AMR. Pharmacists may play an important role in such programmes, as seen in Europe and North America, but the impact, challenges, and opportunities of pharmacist-led antimicrobial stewardship interventions in Sub-Saharan African hospitals are unknown. The purpose of this systematic review was to assess the impact, challenges, and opportunities of pharmacist-led antimicrobial stewardship interventions in Sub-Saharan African hospitals. Methods. The Joanna Briggs Institute (JBI) guidelines were used to search for peer-reviewed pharmacist-led studies based in hospitals in Sub-Saharan Africa that were published in English between January 2015 and January 2021. The PubMed, Embase, and Ovid databases were used. Results. Education and training, audits and feedback, protocol development, and ward rounds were identified as primary components of pharmacist-led antimicrobial stewardship interventions in Sub-Saharan Africa. The pharmacist-led antimicrobial interventions improved adherence to guidelines and reduced inappropriate prescribing, but were hampered by a lack of laboratory and technological support, limited stewardship time, poor documentation, and a lack of guidelines and policies. Funding, mentorship, guidelines, accountability, continuous monitoring, feedback, multidisciplinary engagements, and collaborations were identified as critical in the implementation of pharmacist-led antimicrobial stewardship programmes. Conclusions. These findings suggest that pharmacists in Sub-Saharan African hospitals can successfully lead antimicrobial stewardship programmes but their implementation is limited by lack of mentorship, accountability, continuous monitoring, feedback, collaborations, and poor funding.